TELAAH BUKU TEKS TEMATIK TERPADU KELAS IV SD KURIKULUM 2013 - Ernawati, Yeni (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
Textbooks are learning resources that are used as guidelines or handles in learning activities by students and educators (teachers). As a guide and learning material in learning activities in schools, textbooks must conform the standards of feasibility. Standards for the feasibility of textbooks as learning material, including the feasibility of content, language, and presentation. The results “Tematik Terpadu Kelas IV SD Kurikulum 2013”, namely: a) Feasibility of content: this book is appropriate and in accordance with the curriculum, KI and KD already implied in the textbook material;b) Feasibility of language: this book is feasible by using simple, communicative, and in accordance with the rules of Indonesian language that are good and correct; c) Feasibility of presentation: the presentation of this book is feasible, coherent, and interesting. Material is presented in a coherent manner, from easy to difficult, concrete to abstract. In addition, because this book is used in fourth grade,